O Território e os Riscos: a busca pela resiliência e as inovações no combate às catástrofes ambientais e sociais - Augusto António da Silva, César (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
The theme proposed for this research is related to the search for innovative alternatives, but mainly to examine existing systems for risk prevention and strengthening social resilience in order to make them more just, comprehensive, and effective from the perspective of distributive justice, the rule of environmental law, and under the analytical vision of risks, territorial management, and public policies aimed at promoting technological and legal initiatives in the pursuit of resilience for populations living in urban areas. Case studies on the Brazilian, Portuguese, and European realities will be considered, seeking to analyze international treaties that address environmental, social, and territorial issues.
Keywords: Resilience; Risks; Innovation; Distributive Justice; Rule of Environmental Law